Towards strength-ductility synergy through hierarchical microstructure design in an austenitic stainless steel. (August 2019) - Zheng, Ruixiao; Liu, Maowen; Zhang, Zhe; Ameyama, Kei; Ma, Chaoli
Abstract: An austenitic stainless steel with precisely controlled hierarchical microstructure consisting of statically recrystallized grains (SRGs), nanograins (NGs) and nanoscale twins (NTs) was fabricated by cold rolling (CR) and annealing using pre-sintered powders. The hierarchical structured materials exhibited superior strength-ductility synergy. Comprehensive tensile tests and detailed microstructure observations reveal that the grain boundary strengthening, dislocation source-limited hardening and back stress hardening greatly contribute to the high yield strength. During tensile deformation, the dislocation accumulation, stacking faults and strain induced nanoscale twins appeared in sequence in the SRGs and NTs, giving rise to high strain hardening rate and thus large uniform elongation. Graphical abstract: Unlabelled Image